Infertility in patients with Inflammatory Bowel Disease (IBD): a challenge to overcome - Aab, Arkadiusz; Zarańska, Julia; Miejska-Kamińska, Marta; Kamiński, Filip; Liszka, Adriana (Journal of Education, Health and Sport, 2023)
Introduction: Inflammatory bowel disease (IBD) is a group of chronic digestive disorders that affects an increasing number of people. As the peak incidence of IBD occurs during the reproductive age and affects young people, it is worth examining the impact of IBD on the fertility of patients. In view of the growing problem of infertility in society and the probable relationship between decreased reproductive function and the occurrence of chronic diseases, it is reasonable to examine this phenomenon in detail. Objective: The aim of this study is to summarize the current knowledge on the association between IBD and infertility based on available literature. Materials and methods: A literature review was conducted using PubMed and Google Scholar databases with the following search terms: IBD, infertility, infertility diagnosis, the relationship between IBD and infertility, drugs and infertility, psychological aspects of infertility in IBD. State of knowledge: There are few meta-analyses on the association between IBD and infertility in the literature, and this is due to the small number of studies on this topic. Conclusions: Infertility is becoming an increasingly common problem in people with IBD. Stress and anxiety disorders can have a negative impact on the course of the disease, and thus limit reproductive opportunities. Taking medications to control the course of the disease is crucial for patients to remain in remission, however, patients should be informed about the impact of some medications on reproduction and adjust their conception plans according to their current therapy. Treatment of the underlying disease, reducing anxiety levels, regular physical activity, and a healthy and balanced diet are all components of appropriate management in people with IBD who are trying to conceive. Without these pillars, it is difficult to guarantee successful pregnancy outcomes.